Insurance and Information: Firms as a Commitment Device - A.L. Bovenberg; Coen N. Teulings (Tinbergen Institute, 2001)
We explore the role of firms in insuring non-verifiable output. As a device that allows workers to commit to thedelivery of their output, the firm arises endogenously as an alternative to the market if workers are sufficiently riskaverse and the firm can base its incentive payments on good information. Competition, however, may allow themarket and explicit contracts to crowd out implicit insurance, even though the latter yields higher welfare.Integrating the principal-agent and shirking models, we explain why different contracting modes coexist in quitehomogeneous industries.
Keywords: D23; D82; 330; Insurance; implicit contracts; moral hazard; principal agent; commitment; shirking; Unternehmensversicherung; Information; Prinzipal-Agent-Theorie; Theorie